Concentrations of phthalates and DINCH metabolites in pooled urine from Queensland, Australia. (March 2016) - Gomez Ramos, M.J.; Heffernan, A.L.; Toms, L.M.L.; Calafat, A.M.; Ye, X.; Hobson, P.; Broomhall, S.; Mueller, J.F.
Abstract: Dialkyl phthalate esters (phthalates) are ubiquitous chemicals used extensively as plasticizers, solvents and adhesives in a range of industrial and consumer products. 1, 2-Cyclohexane dicarboxylic acid, diisononyl ester (DINCH) is a phthalate alternative introduced due to a more favourable toxicological profile, but exposure is largely uncharacterised. The aim of this study was to provide the first assessment of exposure to phthalates and DINCH in the general Australian population. De-identified urine specimens stratified by age and sex were obtained from a community-based pathology laboratory and pooled (n = 24 pools of 100). Concentrations of free and total species were measured using online solid phase extraction isotope dilution high performance liquid chromatography tandem mass spectrometry. Concentrations ranged from 2.4 to 71.9 ng/mL for metabolites of di(2-ethylhexyl)phthalate, and from < 0.5 to 775 ng/mL for all other metabolites. Our data suggest that phthalate metabolites concentrations in Australia were at least two times higher than in the United States and Germany; and may be related to legislative differences among countries. DINCH metabolite concentrations were comparatively low and consistent with the limited data available. Ongoing biomonitoring among the general Australian population may help assess temporal trends in exposure and assess the effectiveness of actions aimed at reducing exposures. Highlights: First characterisation of 14 phthalate metabolites and alternatives in Australian population 2400 individual urine specimens pooled by age and sex Australian population concentrations significantly higher than United States and Germany